Metaverse Journalism: Opportunities and Challenges for the Media Industry in Indonesia - Felisianus Novandri Rahmat; Febi Ramadhani Rusdin; Wida Nofiasari (International Journal of Science and Society, 2023)
Metaverse journalism is one of the five formats predicted to become a trend in the future. This was revealed in a survey conducted by Nic Newman in early 2022 to media managers in 52 countries. Even though the presentation is still around 8%, when compared to other formats such as podcasts and digital audio (80%), email newsletters (70%), digital video (63%), voice platform applications (14%), metaverse in the world of journalism deserves attention. Its presence cannot be ignored considering the current condition of society where the majority access information via the internet and social media instead of using conventional media. Coupled with the fact that currently, Indonesia is one of the countries with the most internet and social media users in the world, reaching 212.9 and 167 million users, it is not impossible that this metaverse trend will develop rapidly. For this reason, this study aims to analyze the opportunities and challenges of the metaverse of journalism in Indonesia. The method used in this research is a case study with a qualitative approach. Then data collection was carried out through interviews with informants consisting of the press council, editor-in-chief and journalists. The results of the study show that metaverse journalism does not have the potential to be implemented at this time due to several reasons, namely: there is no universally agreed upon metaverse concept, the technology is still in the development stage, its popularity is being surpassed by AI and currently the audience does not yet exist. Meanwhile, the challenges facing him are the need to increase the capacity of human resources, develop digital infrastructure and formulate standard rules or regulations so that the application of metaverse journalism can have a positive impact.